Strategies for early customer acquisition in a tech startup - R. T. Taschshanov (Путеводитель предпринимателя, 2025)
The article examines effective strategies for attracting early customers in technology startups at an early stage of development. The fundamental concepts of diffusion of innovation, lean startup and product–oriented growth, as well as the international experience of European and American startups are analyzed. It has been shown that successfully attracting early users (early adopters) requires a special approach, different from scaling at mature stages. In the early phase, startups focus on a narrow target audience of innovators, iterative refinement of a minimum viable product using a «create – evaluate – learn» cycle. In addition, tactics such as personal customer interaction, recommendation programs, freemium model, community engagement, and network effects creation are analyzed. It was concluded that the combination of methods focused on achieving PMF (product–market fit) and active dialogue with first customers allows you to achieve product–market compliance and lay the foundation for a scalable business. The materials are based on current research and cases of recent years and are intended for researchers and practitioners interested in strategies for entering startups into the market.